COMPOSITION OF THE NEW DESIGN OF PAYANG CATCHES IN MAJENE WATERS, MAKASSAR STRAIT: Komposisi Jenis Tangkapan Payang Desain Baru Di Perairan Majene, Selat Makassar - Palo, Mahfud; Najamuddin, Najamuddin; Marimba, Andi Assir (Bogor Agricultural University, 2023)
In this study, a new design scottish seine net was used with larger than the general size of the Scottish seine net in the research location. The purpose of this research was to analyze the total catch, species composition and the length of the catch. The study was conducted on one case of a Scottish seine net fishery unit by making a new design of Scottish seine net and then operating it with Scottish seine net fishers in the waters of Majene Makassar Strait. The parameters observed were the fish species caught and the length of each species. From the study results, it was found that the catch of 8 species of fish with total of 15,253 fish in the other bag. The species composition consisted of Shortfin scad (Decapterus macrosoma) 66.48%, Indian mackerel (Rastrelliger kanagurta) 14.42%, Rainbow runner (Elagatis bipinnulata) 7.09%, Mackerel tuna (Euthynnus affinis) 3.83%, Malabar trevally (Carangoides malabaricus) 2.39%, Unicorn leatherjacket (Aluterus monoceros) 2.29%, Skipjack tuna (Katsuwonus pelamis) 2.19% and Goldstripe sardinella (Sardinella gibbosa) 1.31%. The length of the dominant catch Shortfin scad (Decapterus macrosoma) as much as 66.48% ranged from 12.5 - 27 cm with a catchable percentage of 82.53% while Indian mackerel (Rastrelliger kanagurta) as the second highest catch was 14.42% only about 2 ,64% worth catching.